Results of a Culturally Adapted Internet-Enhanced Physical Activity Pilot Intervention for Overweight and Obese Young Adult African American Women. (March 2016) - Joseph, Rodney P.; Pekmezi, Dori; Dutton, Gareth R.; Cherrington, Andrea L.; Kim, Young-Il; Allison, Jeroan J.; Durant, Nefertiti H.
Purpose: This study evaluated a culturally relevant, social cognitive theory–based, Internet-enhanced physical activity (PA) pilot intervention developed for overweight/obese African American (AA) female college students.Design: Using a 3-month, single group, pretest–posttest design, participants accessed a culturally relevant PA promotion website and engaged in four moderate-intensity PA sessions each week.Results: Study completers ( n = 25, mean age = 21.9 years) reported a decrease in sedentary screen time ( p < .0001); however, no changes in moderate-to-vigorous PA were reported ( p = .150). A significant increase in self-regulation for PA ( p < .0001) and marginally significant increases in social support ( p = .052) and outcome expectations ( p = .057) for PA were observed. No changes in body mass index ( p = .162), PA enjoyment ( p = .151), or exercise self-efficacy ( p = .086) were reported.Conclusions: Findings of this exploratory study show some preliminary support for Internet-enhanced approaches to promote PA among overweight/obese AA women.Implications for Practice: Future studies with larger samples are needed to further explore culturally relevant Internet-enhanced PA programs in this underserved population.